Evolution of the Social Web in 2010 - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2011)
Short summary of the Web situation in 2010, analysing the situation of 2.0 technologies and their evolution to adapt to the new conditions of creation of, access to and dissemination of information. Taking into account the Spanish society, the most important changes in 2010 and how they can influence the services that libraries offer are described. Finally, some predictions about 2011 are envisaged.
Keywords: Social networks; Web 2.0; Social Web; Libraries; Library 2.0.